MATH SOLVE

3 months ago

Q:
# Solve by SubstitutionShow Steps−2x + 3y + 5z = −21−4z = 206x − 3y = 0

Accepted Solution

A:

−2x + 3y + 5z = −21
−4z = 20
6x − 3y = 0do -4z=20 firstdivide both sides by -4 to get z by itself-4z/-4=20/-4z=-5Use z=-5 into −2x + 3y + 5z = −21-2x+3y+5(-5)=-21-2x+3y-25=-21move -25 to the other sidesign changes from -25 to +25-2x+3y-25+25=-21+25 -2x+3y=46x-3y=0find x by eliminating yAdd the equations together-2x+6x+3y+(-3y)=4+0-2x+6x+3y-3y=44x=4Divide by 4 for both sides4x/4=4/4x=1Use x=1 into 6x − 3y = 06(1)-3y=06-3y=0Move 6 to the other side6-6-3y=0-6-3y=-6Divide both sides by -3-3y/-3=-6/-3y=2Answer: (1, 2, -5)